Fentanyl nation : toxic politics and America's failed war on drugs - Hampton, Ryan (St. Martin's Press, 2024)
"A passionate call to abandon ineffective drug-war policies, reframe addiction as a public health issue, and end the Fentanyl crisis. The American overdose crisis has reached record-breaking heights; preventable overdoses are now responsible for more annual deaths than traffic accidents, suicide, or gun violence. Fentanyl--a potent, inexpensive, and easy-to-manufacture synthetic opioid--has thoroughly contaminated the drug supply, and while it frequently makes front page news across the country, it remains poorly understood by policymakers and the public. Why, despite all of our efforts to raise awareness and billions of dollars of investments, does this emergency keep getting worse? In Fentanyl Nation, recovery advocate Ryan Hampton separates the facts from the fiction surrounding Fentanyl, and shows how overdose deaths are ultimately policy failures. Instead of investing in education, harm reduction, effective treatment, and recovery, we have doubled down on more police, more incarceration, and harsher penalties for those caught in the grip of addiction. Yet history has shown time and time again that it is impossible to arrest our way out of a public health crisis; the government used the same strategy to fight the crack-cocaine epidemic of the 80s and 90s, and it only resulted in racially disparate policing and the destruction of marginalized communities. This urgent and informative manifesto reveals how prejudice, discrimination, and stigma have been codified into our drug laws, and calls for a compassionate and evidence-based approach that would address the core causes of addiction and save countless lives. We can end this crisis, but only if we get out of our own way"--